Changes of Soil Physical and Chemical Characteristics of Vertisol by Organic Matter and Sands Applications - Wanti - Mindari; Purnomo Edi Sasongko; Setyo Budi Santoso (UNIVERSITY OF LAMPUNG, 2023)
Vertisol has a clay texture, high micropores, and high water and nutrient absorption ability. The high water content of Vertisol causes the air to decrease, thus inhibiting root development. Stretching of the Vertisol structure is expected to increase soil porosity and reduce ion and water absorption. This study examines interactions between organic matter and percent sand on soil porosity and nutrient availability. The study was arranged according to a factorial Completely Randomized Design (CRD), repeated three times. The first factor was seven kinds of organic matter (control, cow dung + banana peel compost, cow dung + leaf litter compost + compost water hyacinth + cow dung, humin, humic acid, and biochar. The application doses are respectively for each treatment: humic acid and humin 20 kg ha-1, biochar 1 Mg ha-1, compost+manure fertilizer 15 Mg ha-1. Changes in soil chemical characteristics were evaluated against pH, C-org, and Available-P, while changes in soil physical characteristics were evaluated against bulk density, particle density, and soil porosity. The results showed that the combination of organic matter and percent sand could improve the physical and chemical characteristics of the soil. Bulk density (BD), particle density (PD), and soil porosity increased with the addition of sand. The organic matter significantly correlated with improving soil properties was humic acid, humin, biochar, compost, and manure, with the best percentage of sand at 20%.